Evaluation of the Settling Basin of Keumala Weir, Krueng Baro River, Aceh, Indonesia - Azmeri Azmeri; Henny Herawati; Nur Aisya Amalia; Faris Zahran Jemi (Graduate Program of Syiah Kuala University, 2019)
Krueng Baro Irrigation network is a strategic technical irrigation area in Pidie, Aceh, Indonesia. The primary water source is the Krueng Baro River flow using the infrastructure of Keumala Weir in which sedimentation is currently a significant problem in its operations. To prevent the sediment from entering the irrigation channel is to settle it in the settling basin. However, the primary irrigation channel with the stone masonry walls kept experiencing high sedimentation. Therefore, this study aimed to evaluate the performance of the Keumala Weir settling basin including its capacity and efficiency. This study used a survey method for data collection and an evaluation method following the current guidelines for data analysis. The sediment sampling was conducted in the settling basin and the primary channel. The flushing was currently carried out for seven days. However, the settling basin capacity of 2,436.75 m3 did not meet the flushing requirements. Thus, the flushing should be performed daily for a volume of 1,859.43 m3 to fulfill the condition, so that the capacity of the settling basin was controlled. The efficiency of sediment settling was 75%, and the effect of water turbulence was in a safe condition, that the sediment settled in a settling basin would not be eroded when it is empty or full. For the flushing efficiency, the shear stress was 15,538 N/m2 that can rinse less than 16 mm particles. Based on this evaluation, it can be concluded that the sediments in the primary channel were from the settling basin. It is suggested to limit the speed in the regulating building to approximately 1.5 m/s to reduce the sediments entering the primary channel. It also requires accuracy in the operation of the primary channel intake.